Pengaruh Resonansi Merek, Kepercayaan Merek dan Citra Merek Terhadap Loyalitas Konsumen Pengguna Produk Handphone Samsung - Fanny, Dhevan Muhammad; Murwanti, Sri (STIE AMKOP, 2023)
Introduction/Main Objectives: The purpose of this study was to analyze the effect of brand resonance, brand trust, and brand image on consumer loyalty of Samsung mobile phone product users. Background Problems: The high demand for Samsung products in Sukaharjo district makes smartphone brand competition tighter, this is what affects customer loyalty in buying the Samsung smartphone brand offered. Novelty: This research is a very relevant step to understand more about Samsung smartphones, especially in the context of influencing factors such as brand resonance, brand trust, and brand image. Research Methods: This research is a study that uses a type of quantitative approach, the sampling technique in this study is non probability sampling with purposive sampling technique. The number of respondents in this study were 100 people and processed using the SMARTPLS 3.0 analysis technique. Finding/Results: Brand Resonance, Brand Trust and Brand image have a positive effect on customer loyalty. Conclusion: Brand resonance creates a deeper experience, strengthening the bond between consumers and the brand, brand trust can be the key to creating long-term consumer loyalty and the relationship between brands and consumers, Customer loyalty can be built through improving brand image, among others, through a good impression, attractive products, and have uniqueness.